Does the healthy plate model workshop improve nutrition knowledge, behaviors, and habits in school-age children? The impact of workshop on dietary habits - Hatice Şimşek Şahin; Volkan Özkaya (BMC Public Health, 2025)
Abstract Background This study was conducted to identify the impacts of the healthy plate model workshop on 4th-graders nutrition knowledge, behaviors, and habits. Methods The study was conducted from March to June 2023 in the Uskudar district of Istanbul, involving 102 children (50% girls) with a mean age of 10.2 ± 0.45 years. A pretest-intervention-posttest design was used for the research. Before and after the training, a questionnaire was administered to measure students’ demographic characteristics, physical activity status, adherence to the Mediterranean Diet, frequencies of food group consumption, and nutritional knowledge. Results The number of students consuming eggs, legumes, vegetables, fruits, and oilseeds daily increased after the training (p > 0.05). Increases were observed in daily consumption of meat group and water (p < 0.05). While the proportion of students who consumed whole fruit with skin was 35.3% before the training, this rate increased to 47.1% after the training (p < 0.05). The mean nutritional knowledge score (before: 71.37 ± 11.8; after: 80.45 ± 1.6, p < 0.05) and the Mediterranean Diet Quality Index (KIDMED) score (before: 4.77 ± 2.41; after: 5.50 ± 2.45, p < 0.05) increased significantly after the training. A weak positive correlation was identified between pre-training nutritional knowledge scores and KIDMED index scores (r = 0.19; p = 0.045). Furthermore, a negative weak relationship was observed between post-training nutritional knowledge scores and meal-skipping status (r=-0.231; p = 0.019). Conclusions Structured nutrition education for school-age children can positively impact their nutritional knowledge and dietary habits.